2016
DOI: 10.1016/j.ygyno.2016.08.335
|View full text |Cite
|
Sign up to set email alerts
|

Electronic patient-reported outcomes from home in patients recovering from major gynecologic cancer surgery: A prospective study measuring symptoms and health-related quality of life

Abstract: Purpose We previously reported on the feasibility of a Web-based system to capture patient-reported outcomes (PROs) in the immediate postoperative period. The purpose of this study was to update the experience of these patients and assess patient and provider satisfaction and feedback regarding the system. Methods This is a prospective cohort study of patients scheduled to undergo laparotomy for presumed gynecologic malignancy. Patients completed a Web-based Symptom Tracking and Reporting (STAR) questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
1
44
1
Order By: Relevance
“…Standardized reporting is now available through the National Cancer Institute's Patient‐Reported Outcomes‐CTCAE (PRO‐CTCAE) scales . Efforts are underway to integrate PRO‐CTCAE measurement into clinical trials , and interest is growing in the implementation and utilization of patient‐reported symptom monitoring in patient‐centered clinical practice . Like CTCAE, the focus of PRO‐CTCAE is continuous symptom monitoring throughout chemotherapy, not just at the beginning and end of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized reporting is now available through the National Cancer Institute's Patient‐Reported Outcomes‐CTCAE (PRO‐CTCAE) scales . Efforts are underway to integrate PRO‐CTCAE measurement into clinical trials , and interest is growing in the implementation and utilization of patient‐reported symptom monitoring in patient‐centered clinical practice . Like CTCAE, the focus of PRO‐CTCAE is continuous symptom monitoring throughout chemotherapy, not just at the beginning and end of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite positive feedback from patients, clinical personnel found that STAR system increased their current workload without enhancing patient care. 43 Although the results of those two feasibility studies are promising, we want to emphasise the importance of targeting the entire surgical pathway from the early preoperative phase, starting when the indication for surgery is set, until the late postoperative phase, ending with full recovery and resumption of all daily activities, in which our own internet-based care programme is unique.…”
Section: Discussionmentioning
confidence: 99%
“…PROs were added to this table when used in 3 or more papers. In this review, the most commonly used validated PRO questionnaire for collecting HRQoL data is the EORTC QLQ-C30, used in 28% of the 50 included papers [10][11][12][13][14][15][16][17][18][19][20][21][22]. It is a European widely used core generic questionnaire for cancer patients, and comprises most dimensions of wellbeing as described by Linton et al [6], excluding spiritual wellbeing and personal circumstances.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
“…The Functional Assessment of Cancer Therapy -General (FACT-G), also a cancer-specific HRQoL questionnaire is more frequently used in America, but was less frequently used for data collection --in 6% of included papers [36][37][38]. The second most used questionnaire in this review was Patient-Reported Outcomes Measurement Information System (PROMIS), a set of person-centered measures (enabled by CAT and IRT), used in 16% of the papers [12,14,16,[22][23][24][25][26]. Third most used (8%) questionnaire was the EQ-5D-5L [19[21,27-30] questionnaire that can be used to compute Quality-adjusted Life Years (QALY's), a generic measure of disease burden, including both the quality and the quantity of life lived.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation